Prolyl-4-Hydroxylase 2 Potentially Contributes to Hepatocellular Carcinoma-Associated Erythrocytosis by Maintaining Hepatocyte Nuclear Factor-4α Expression - Wenwen Sun; Friederike Katharina Kosyna; Wolfgang Jelkmann; Reinhard Depping (Cellular Physiology and Biochemistry, 2015)
Background: Increased red blood cell count (Erythrocytosis) is an important paraneoplastic syndrome of hepatocellular carcinoma (HCC) and is a significant risk factor for lethal lung artery thromboembolism. HCC-associated erythrocytosis is partially caused by the ability of several HCC cells to produce erythropoietin (EPO). Prolyl-4-hydroxylase 2 (PHD2) is an enzyme encoded by the gene EGLN1. The best-known function of PHD2 is to mediate the oxygen-dependent degradation of the labile α-subunit of hypoxia-inducible factor (HIF). However, there is increasing evidence that PHD2 also regulates HIF-independent pathways by interacting with other substrates. Methods: In the EPO-producing human HCC cell line HepG2, the expression of PHD2 gene was silenced with siRNA. EPO production was estimated using quantitative PCR and ELISA. Results: In HepG2 cells, PHD2 suppresses the activity of TGF-β1 pathway and consequently maintains the expression of hepatocyte nuclear factor-4α (HNF-4α), an important transcription factor promoting the EPO expression in hepatocytes. PHD2 knockdown caused a marked reduction of EPO production. HIF seemed not to be involved in this biology. Conclusion: Our findings show that PHD2 represents a potential contributing factor for HCC-associated erythrocytosis. Selective inhibition of PHD2 in HCC cells might be considered as a new way to manage erythrocytosis in HCC patients.